'Stranger-danger' – Israeli children playing with the concept of 'Corona' and its' impact during the COVID-19 pandemic. Issue 4 (2nd October 2021) - Cohen, Esther; Bamberger, Esther
ABSTRACT: This study examines reports of 118 parents about the play activities of Israeli children aged 3-9 during the COVID-19 pandemic. Parents responded to online questionnaires describing children's play, creative activities and the family's situation. Qualitative analyses revealed changes in both the nature of the children's play activities and in the expressed themes. Findings highlight positive gains in children's development and family relationships. The varied and expansive nature of play seemed to support the children's coping with lockdown and social distancing restrictions. Themes emerging from socio-dramatic play show attempts to deal with fear of coronavirus by seeking imaginary protection and refuge from it, and by attempts to defeat it. Of note are the use of humor and cynicism alongside acts of concern and altruism towards grandparents. Our study contributes evidence as to the adaptive abilities of children and the self-healing functions of play, and denote the need to promote them.